N-acetyltransferase 2 phenotype, occupation, and bladder cancer risk: results from the EPIC cohort. - Pesch, B; Gawrych, K; Rabstein, S; Weiss, T; Casjens, S; Rihs, H; Ding, H; Angerer, J; Illig, T; Klopp, N; Bueno-de-Mesquita, B; Ros, M; et al. (2013)
BACKGROUND: An association between N-acetyltransferase 2 (NAT2) slow acetylation and bladder cancer has been consistently observed in epidemiologic studies. However, evidence has been mainly derived from case-control studies and was sparse from cohort studies. We evaluated the association between NAT2 slow acetylation and bladder cancer in a case-control study nested in the European Prospective Investigation into Cancer and Nutrition. METHODS: Exposure to aromatic amines and polycyclic aromatic hydrocarbons (PAH) could be assessed for 754 cases and 833 controls for whom occupational information was documented. A semiquantitative job-exposure matrix was applied to at-risk occupations to estimate the exposure as low, medium, or high based on tertiles of the distribution of the exposure score in controls. Using a comprehensive genotyping, NAT2 acetylation status could be categorized from 6-single-nucleotide polymorphism genotypes as slow or fast in 607 cases and 695 controls with DNA from archived blood samples. RESULTS: Occupational exposure to aromatic amines and PAH was associated with an increased bladder cancer risk [upper tertile of the distribution of the exposure score: OR = 1.37; 95% confidence interval (CI), 1.02-1.84, and OR = 1.50; 95% CI, 1.09-2.05, respectively]. NAT2 slow acetylation did not modify these risk estimates and was not itself associated with bladder cancer risk (OR = 1.02; 95% CI, 0.81-1.29). CONCLUSIONS: These findings confirm established or suspected occupational risk factors but not the anticipated role of NAT2 slow acetylation in bladder cancer. No interaction was detected between NAT2 and any exposure of interest, including smoking. IMPACT: Genetic testing for NAT2 would be inappropriate in occupational settings.